A comparison of three different orthognatic surgery methods on the range of mandibular movements - Refoua Y; Jalayer S (Tehran University of Medical Sciences, 2002)
Dept. of Oral and Maxillofacial Surgery, Ghazvin University of Medical Sciences A lot of studies have discussed the reduction of mandibular movements range after orthognatic surgeries. The present study focuses on the conventional orthognatic surgery methods to determine the method with the least effects on mandibular movements. Sixty patients were investigated in a prospective study. They were divided, based on the surgical method, into three groups. In the first group (20 patients) sagital osteotomy, in the second group extra oral vertical osteotomy for mandibular retrusion, and in the third group simultanouse Bimax osteotomies of the upper and lower jaws, were performed. The surgical method applied for maxilla was Lefort 1 osteotmy to protrude the upper jaw and of the lower jaw was extraoral vertical osteotmy. The range of mouth opening, in centrals region, right and left lateral movements and protrusive movements, before and three months after surgery, were measured. Sagital osteotomy method (the first group) showed the most changes and reduction in movements, while the least changes were observed in extraoral vertical method (the second group).